Late neonatal presentation of reduced arm movement due to painful infective lymphadenopathy. (7th July 2015) - Stokes, Victoria; Fertleman, Caroline
Abstract : We report two cases of 21-day-old male infants, Baloo and Bagheera, both admitted with unilateral reduced arm movement secondary to painful lymphadenopathy, which is a presentation previously unreported in the paediatric literature. The only abnormal finding following investigations in both neonates was infective lymphadenopathy; we hypothesise that the inflamed lymph nodes were tender when the surrounding muscles, fascia or skin were moved, so that the infants learnt to reduce arm movement to minimise pain. This report explores the differential diagnoses for reduced arm movement in neonates, and highlights the importance of sepsis with painful lymphadenopathy as a differential diagnosis in neonates presenting with reduced arm movement.